Management Control in Public-Private Partnerships Between International Governmental Actors and the Private Sector - Konrad, Thomas S. (Schriften zu Wirtschaftsprüfung, Steuerlehre und Controlling, 2018)
Thomas S. Konrad analyzes the management control design and reveals critical success factors of strategically oriented public-private partnerships for development between international governmental actors and the private sector. He builds a sound basis for the identification of a research gap and the derivation of research questions. The results generate sufficient evidence to answer these questions and therefore to close the identified research gap. Finally, he excelled in the discussion of the results by making a contribution of theory and by providing substantive recommendations to practitioners equally well. Contents Basics of Management Control in Public-Private Partnerships (PPPs) Control Archetypes and Typologies Actor-Centered Institutionalism Transaction Cost Economics Basic Characteristics of PPPs for Development Partnership Setting Target Groups Researchers and students in the field of economic science with focus on controlling Practitioners in this area The Author Dr. Thomas S. Konrad wrote his dissertation under the supervision of Prof. Dr. Andreas Hoffjan at TU Dortmund University.